THE EFFECT OF UNDERCOVER GAME ON STUDENTS’ VOCABULARY ACHIEVEMENT - Lukas Wiliam Cooper Lukas; Eusabinus Bunau; Surmiyati (Esteem Journal of English Education Study Programme, 2024)
The purpose of this study was to find out if eleventh-grade students at SMA Negeri 10 Pontianak's usage of the Undercover Game app affected their vocabulary success in the 2022–2023 academic year. In this study, a pre-experimental design was used. Thirty-two students studying social science made up the sample. Data from the pre- and post-tests were gathered, and a t-test was used for analysis. Twenty-five multiple-choice questions with four possible answers (a, b, c, and d) comprised the test. The post-test result was 2488, but the pre-test result was 2080. The data shows that the t-test result was 18.21. For thirty-one samples, the t table with 5% degree of freedom (df) is 2.039. The alternative hypothesis (Ha) is accepted based on the data analysis shown above, and the null hypothesis (H0) is rejected because the t-test result is greater than the value indicated in the t-table (18.21>2.039). Furthermore, the effect size is 3.09, falling into the high effect (>0.8) category. In summary, there was a significant impact on students' vocabulary achievement when the Undercover Game programme was implemented. For this reason, Undercover Game comes highly recommended as a useful instrument for improving vocabulary in students.